1997
DOI: 10.1016/s1074-5521(97)90300-8
|View full text |Cite
|
Sign up to set email alerts
|

Bi-stranded, multisite replication of a base pair between difluorotoluene and adenine: confirmation by ‘inverse’ sequencing

Abstract: The results confirm that F in a template strand encodes the insertion of dATP and that adenine in a template encodes the insertion of dFTP with good specificity in at least six different nearest neighbor contexts. The results confirm that analog F behaves similarly to thymidine despite its poor hydrogen-bonding ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
3

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 15 publications
2
39
0
3
Order By: Relevance
“…In this model, a wrong nucleotide cannot be positioned properly for the nucleophilic attack in the active site of the polymerase, and this slows down the rate of the bond formation significantly. The major role of the base pair geometry in replication has been confirmed recently by Kool and co-workers (19,20), who showed that a thimidine triphosphate shape analog lacking Watson-Crick pairing ability is replicated with high sequence selectivity.…”
mentioning
confidence: 75%
“…In this model, a wrong nucleotide cannot be positioned properly for the nucleophilic attack in the active site of the polymerase, and this slows down the rate of the bond formation significantly. The major role of the base pair geometry in replication has been confirmed recently by Kool and co-workers (19,20), who showed that a thimidine triphosphate shape analog lacking Watson-Crick pairing ability is replicated with high sequence selectivity.…”
mentioning
confidence: 75%
“…[116] Ironically, the DNA being synthesized was less stable than the natural DNA by a significant amount. Clearly, however, the DNA polymerase does not sense this destabilization until after the transition REVIEWS E. T. Kool et al Figure 7.…”
Section: Studies With Nonpolar Thymine Analogue Fmentioning
confidence: 99%
“…Interestingly, the DNA polymerase does apparently sense destabilization when multiple F ± A pairs are being synthesized in a row. [116] We suspect that this might arise from the enforced desolvation of the F ± A pairs when they become buried further into the active site.…”
Section: Studies With Nonpolar Thymine Analogue Fmentioning
confidence: 99%
“…However, when a run of three adenines was addressed by insertion of analog dFTP, it was found that the second and third adenines presented successively increasing difficulty to the enzyme, and a nearly complete stall was observed after the third apparent insertion of A. 74 Two possible reasons for this observation have been presented: first, the destabilization caused by F-A pairs is likely to be large when they are placed in a run, and this may result in dissociation of primer from template and of polymerase from both. Another possible reason may be poor extension of such pairs, which is typically less favorable than insertion.…”
Section: Prospects For Synthesis Of Dna Strands Without Hydrogen Bondsmentioning
confidence: 99%